Reversible guest-induced gate-opening with multiplex spin crossover responses in two-dimensional Hofmann clathrates. Issue 41 (28th September 2020) - Turo-Cortés, Rubén; Bartual-Murgui, Carlos; Castells-Gil, Javier; Muñoz, M. Carmen; Martí-Gastaldo, Carlos; Real, José Antonio
Abstract : Layered Hofmann-type iron(ii ) coordination polymers functionalised with 5-aminopyrimidine ligands show gate-opening driven guest-exchange accompanied by drastic structural and spin-crossover modulations. Abstract : Spin crossover (SCO) compounds are very attractive types of switchable materials due to their potential applications in memory devices, actuators or chemical sensors. Rational chemical tailoring of these switchable compounds is key for achieving new functionalities in synergy with the spin state change. However, the lack of precise structural information required to understand the chemical principles that control the SCO response with external stimuli may eventually hinder further development of spin switching-based applications. In this work, the functionalization with an amine group in the two-dimensional (2D) SCO compound Fe(5-NH2 Pym)2 [M II (CN)4 ] (1 M, 5-NH2 Pym = 5-aminopyrimidine, M II = Pt (1 Pt ), Pd (1 Pd )) confers versatile host–guest chemistry and structural flexibility to the framework primarily driven by the generation of extensive H-bond interactions. Solvent free 1 M species reversibly adsorb small protic molecules such as water, methanol or ethanol yielding the 1 M ·H2 O, 1 M ·0.5MeOH or 1 M · x EtOH ( x = 0.25–0.40) solvated derivatives. Our results demonstrate that the reversible structural rearrangements accompanying these adsorption/desorption processes (1 M ↔ 1 M ·guest ) follow a gate-opening mechanism whose kinetics depend not only on the nature of the guest molecule and that of the host framework (1 Pt or 1 Pd ) but also on their reciprocal interactions. In addition, a predictable and reversible guest-induced SCO modulation has been observed and accurately correlated with the associated crystallographic transformations monitored in detail by single crystal X-ray diffraction.